NNOVATIVE AND TECHNOLOGICAL CAPACITY OF MINING REGIONS OF RUSSIA AND MECHANISMS OF HIS REALIZATION (on the example of the Kemerovo region) - E. V. Shavina; O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Transition to innovative economy becomes a characteristic tendency of modern development of many countries. A characteristic trend of the modern development of many countries is the transition to an innovative economy. And for Russia the innovation-technological development of its regions is important. The authors outline five main indicators that help determine the level of innovation and technological development of one of the largest industrial regions of Russia - the Kemerovo region. The special role of the Kemerovo region as a large territorial production complex of Western Siberia requires large-scale work to address the most acute regional problems. The system of state measures aimed at making the innovation component a leading factor in the competitiveness of the regional economy should include the development of a long-term innovation strategy, the improvement of the innovation infrastructure, the creation of a financing system for innovation, the attraction of highly qualified personnel to the innovation sphere and the strengthening of interregional and international innovation and technological cooperation, in particular with the BRICS and EEU.  Keywords: innovative and technological development, innovations, mining region, innovative economy, Kemerovo region, mining industry, industrial policy.